Multiple Genome Sequences of the Important Beer-Spoiling Species Lactobacillus backii - Geissler, Andreas J. (Genome Announc, 2016)
Lactobacillus backii is an important beer-spoiling species. Five strains isolated from four different breweries were sequenced using single-molecule real-time sequencing. Five complete genomes were generated, which will help to understand niche adaptation to beer and provide the basis for consecutive analyses.